Review Artikel : Aktivitas Antikanker dari Spons Laut Genus Xestospongia - Asniar Pascayantri, Adryan Fristiohady,Prahedi Setya Ibrahim (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2021)
Abstract            The discovery of novel agents in the treatment of cancer is still being conducted, one of them is by developing the marine natural resources as an anti-cancer drug. Sponges like the genus Xestospongia, are natural marine resources that have potential as anti-cancer. Thus,, this review aims to showing the potential of the genus Xestospongia as an anticancer. This review was carried out by collecting the literature from various databases from 2014 to 2019. Results obtained that marin sponge Xestospongia, including Xestospongia testudinaria, Xestospongia exigua, Xestospongia muta and Xestospongiawiedemayeri, were used as anticancer. These compounds such as Quinolizidine, Aragusterol, Araguspic and many more.Keywords— Xestospongia, anticancer, cytotoxicity Abstrak            Penemuan obat baru dalam pengobatan kanker masih intensif dilakukan, salah satunya dengan pengembangan sumber daya alam laut sebagai obat anti kanker. Spons seperti genus Xestospongia, merupakan sumber daya alam laut yang memiliki potensi sebagai anti kanker. Oleh karena itu, review ini bertujuan untuk menunjukkan potensispons genus Xestospongia sebagai antikanker. Review ini dilakukan dengan mengumpulkan pustaka dari berbagai database dari tahun 2014 hingga 2019. Hasil yang didapatkan bahwa spesies dari Xestospongia seperti Xestospongia testudinaria, Xestospongia exigua, Xestospongia muta dan Xestospongia wiedemayeri tercatat berpotensi sebagai antikanker. Senyawa-senyawa tersebut seperti Quinolizidine, Aragusterol, Araguspic dan masih banyak lagi.Kata Kunci— Xestospongia, antikanker, sitotoksisitas